Online Service Delivery in Survey Offices: Step towards e-Land Administration - Dangol, Susheel; Joshi, Prakash; Dahal, Tanka Prasad (Journal on Geoinformatics, Nepal, 2020)
Survey Offices established at the districts under Survey Department are supporting with cadastral survey and the updating the parcels according to the land transactions. Almost all of the district offices among 131 of such are conducting its daily activities in digital environment. At present all the district survey offices have their own server and individual desktop applications are running to conduct the daily activities. In the recent development, Survey Department has developed three tier client-server based system architecture where application and database server are managed in central server hosted in Government Integrated Data Centre and clients access these server to provide the service. This system has enabled to integrate all the cadastral data from district survey office to single central archive. “Nepal Land Information System (NeLIS)” for daily service delivery from the survey offices and “MeroKitta” to get online service facility from survey offices has been developed and implemented in few numbers of the survey offices and planned to replicate in further offices.